IMPROVING QUALITY OF SERVICE BASED ON CUSTOMER SATISFACTION USING SERVQUAL AND QFD METHODS AT SEJAHTERA BUANA TRADA PULOGADUNG (ATPM X) - Mohammad Rachman Waluyo (Prosiding Seminar Nasional Waluyo Jatmiko, 2026)
This study discussed the assessment of service quality provided by Sejahtera Buana Trada Pulogadung. The purpose of this research was to design an effective service model that could be used by the company to enhance its existing service standards. The scope of the study included measuring customer satisfaction levels and identifying service attributes that require improvement. The research employed the Service Quality approach and Quality Function Deployment method based on the House of Quality model. The integration of these two approaches was used to analyze and design service quality improvements at Sejahtera Buana Trada Pulogadung. The results showed that reliability was the main service variable that needed to be prioritized for improvement. Based on the integration of the Service Quality and Quality Function Deployment methods, the company needed to ensure timely service delivery according to expected work schedules. Furthermore, the findings indicated that implementing a customer relationship management system, conducting regular employee training, applying standard operating procedures, managing human resources, and improving service facilities were essential technical actions to enhance and maintain service quality sustainably.